Udlevering af lovovertrædere – en retshistorisk undersøgelse af retsgrundlaget og nogle statsretlige overvejelser - Ole Terkelsen (Nordisk Tidsskrift for Kriminalvidenskab)
This article examines the legal framework for Danish extradition as practiced prior to the first extradition acts from the 1960s. First, the article describes the development of international extradition law from a Danish perspective. Agreements regarding extradition can be found in Danish treaties dating back several hundred years. Second, the article analyses the Danish legal basis of extradition. The lack of legislation until the 1960s has often been criticized by legal scholars, but the topic has not been studied in depth before. The early Danish extradition practice raises fundamental legal questions regarding inter alia the legal protection of foreigners in Denmark, the scope of the principle of legality, and the interpretation of the provisions of the Danish constitution relating to the deprivation of liberty.